AsthmaWise – a field of dreams? The results of an online education program targeting older adults with asthma. (20th June 2013) - Burns, Pippa; Jones, Sandra C.; Iverson, Don; Caputi, Peter
Abstract: Objectives : The aim of this study was to establish the feasibility and acceptability of an online asthma self-management program developed for older Australians with asthma. Methods : AsthmaWise, an internet education self-management program, was piloted for a 3-month period at the beginning of 2012. Participants were recruited using both online and offline strategies and were required to complete surveys, both pre- and post-intervention, in a repeated measures design. Results : Matched data were collected from 51 participants; the results showed AsthmaWise to be a feasible and acceptable method of delivering asthma education to the target population. Self-reported measures showed an increase in participants' asthma knowledge, asthma control and quality of life. Results from the Perceived Health Web Site Usability Questionnaire (PHWSUQ) showed improvements between usability testing and implementation. Conclusion : The need for asthma self-management education will continue to increase as the population ages and a greater number of older adults are living with asthma. This small pilot study indicates that an online asthma self-management education program can result in improved outcome measures in a target group not normally considered technologically literate.